Numerical Study on Turbulent Forced Convection and Heat Transfer Characteristic in a Circular Tube with V-Orifice. (15th May 2017) - Jedsadaratanachai, Withada; Boonloi, Amnart
Abstract : Performance assessments on heat transfer, pressure loss, and thermal enhancement factor in the circular tube heat exchanger inserted with the V-orifices are investigated numerically. The influences of the blockage ratio, gap spacing ratio, and orifice arrangement are reported for turbulent regime, R e = 3000 – 10, 000 . The finite volume method and SIMPLE algorithm are selected to solve the present problem. The mechanisms on flow and heat transfer characteristics are described. The periodic concepts on flow and heat transfer are also studied. The numerical results show that the gap spacing ratio is main reason for the changes of the flow and heat transfer topologies. The gap distance helps to adjust the optimum point of the thermal performance, especially at high flow blockage ratio. In addition, the optimum thermal performance of the present system is around 2.25 at the lowest Reynolds number, R e = 3000 .